Critical peer feedback for business English writing through Qzone blogs: a mechanism among Chinese undergraduates - Gao, Xianwei; Adelina Asmawi,; Samuel, Moses (Penerbit Universiti Kebangsaan Malaysia, 2017)
This study explored critical peer feedback with critical thinking to improve Business English writing. Higher-order thinking skills in peer feedback is conducted to facilitate higher-level writing. This study focuses on the participants’ mechanism of critical peer feedback, Qzone blog for critical peer feedback, and issues in critical peer feedback. A qualitative case study is conducted with six Chinese undergraduates. Three kinds of data including semi-structured interviews, Business English writing assignments and artifacts of critical peer feedback, are analyzed by QSR Nvivo 8. The findings reveal that critical peer feedback is a strategy of higher-order peer feedback to improve the higher-level writing. The Revised Bloom’s Taxonomy is accepted for critical peer feedback. Critical peer feedback improves the quality of peer feedback and the quality of Business English writing. Qzone blog is a convenient ICT platform for critical peer feedback with many strengths. However, six issues are also perceived in the practice of critical peer feedback. The finding is significant to the process of critical peer feedback in second language writing.